The dynamics of apple-planted areas, apple production and apple prices in Romania - Ancuța Marin (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 9th Edition of the International Symposium, November 2018, Bucharest, 2018)
The diversified way of eating apples as well as the versatility of the species that can be cultivated with good results under different environmental and climatic conditions has determined a particular interest for fruit growers. In Romania, apple culture occupies the first place both in terms of surface and production. Current concepts of rational nutrition place fruit consumption in a priority, primarily because they provide the human body with a wide range of vitamins, mineral salts and vital water that are so necessary for the normal physiological activity of the human body. In this paper we are looking at the dynamics of the areas planted with apple during the period 2010-2016, the dynamics of the total and average outputs, as well as the dynamics of the capitalization prices on each county. The purpose of the paper is to make some recommendations that might be useful to Romanian producers who choose apple for their business.
Keywords: Q13; Q11; O13; 330; production; apple; production dynamics; capitalization prices